Macroeconomic risk influences on the KLSE property index / Noorlelawati Baharuddin - Baharuddin, Noorlelawati (2014)
The study is an attempt to investigate the macroeconomic risk influences on the KLSE Property Index due to the limited literature provided especially in Malaysia. The variables that are considered in this study are gross domestic product (GDP), interest rate (INTR), exchange rate (EXC) and money supply (MS). The sample of this study comprises of 40 observations which each of the independent and dependent variables are taken on a quarterly basis over a 10 year period from 2003 to 2012. For the data treatment purpose, this study used a methodology Multiple Linear Regression with time series data sources from Data Stream and EIU Country Data. Thereafter, econometric tests are conducted to observe the relationship of the macroeconomic risks toward the KLSE Property Index. An interactive software package Eviews7 is used for testing and analyzing the data collected. The results of this research paper will provide an indicative view and could form an important basis for the investors and policy makers in order to make an investment decision for their portfolio.